Relationship between malaria vector survival, infectivity, and insecticide-treated net use in western Kenya - Lucy Abel; Emma Kimachas; Evans Omollo; Erick Nalianya; Tabitha Chepkwony; Joseph Kipkoech; Mark Amunga; Aggrey Wekesa; Jane Namae; Samuel Kahindi; Judith Mangeni; Zena Lapp; et al. (Parasites & Vectors)
Abstract Background Significant effort and resources have been invested to control malaria transmission in sub-Saharan Africa, but it remains a major public health problem. For the parasite to be transmitted, the female Anopheles vector must survive 10–14 days following an infective bite to allow Plasmodium gametocytes to develop into infectious sporozoites. The goal of this study was to assess factors associated with wild-caught Anopheles survival and infection following host-seeking and indoor resting. Methods The study was conducted between January 2020 to March 2022 in a longitudinal cohort of 75 households in 5 villages including a total of 755 household members in Bungoma County, Kenya. Monthly adult mosquito collection was conducted by attenuated aspiration in all enrolled households, and mosquitoes were reared for 7 days. The daily mortality rate was determined through day 7. All mosquitoes were morphologically identified. Female Anopheles were dissected, and species-level members of the Anopheles gambiae complex were resolved by molecular methods. The abdomens of all samples were processed for Plasmodium falciparum oocyst detection by PCR. Results Within a 25-month period, the total numbers of non-Anopheles and Anopheles mosquitoes collected indoors were 12,843 and 712, respectively. Anopheles gambiae and An. funestus were the major vectors, though their distributions varied between different villages; 61.2% (n = 436/712) of the Anopheles mosquitoes survived up to day 7, with the lowest mortality rate recorded on day 5 of captivity. The survival rate also varied between the different Anopheles species. Six hundred eighty-three of 712 mosquito abdomens were tested for P. falciparum; 7.8% (53/683) tested positive for P. falciparum, with An. funestus having a higher (10%) prevalence than An. gambiae s.s. (6.0%, p = 0.095, Pearson Chi-square test). The proportion of household members sleeping under a bednet the night before mosquito collection varied across time and village. Anopheles funestus survival times were refractory to household ITN usage, and An. gambaie s.s. survival was reduced only under very high (100%) ITN usage. Conclusions Despite ITN usage, mosquitoes still acquired blood meals and P. falciparum infections. Survival differed across species and was inversely correlated with high ITN usage in the household but not oocyst development. Graphical Abstract